(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Influence of amino acids (L-glycine, L-alanine, L-phenylalanine, L-serine, L-aspartic acid, L-lysine and L-leucine) on the critical micelle concentration (cmc) and thermodynamic of micellization of nonionic surfactant hexadecyl poly[oxyethylene(25)] alcohol (C16A25) in aqueous solutions at different temperatures was studied. It was shown that with the increase of amino acids concentration cmc of C16A25 decreased, and with the increase of the temperature cmc of C16A25 increased.